Relationship between Knowledge and Supervision with Unsafe action in Practical Workshop of State Vocational School Students in Medan City - Fadli Fadhilah Banurea; R Kintoko Rochadi; Isyatun Mardhiyah Syahri (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Vocational High School (VHS) is an educational institution with various practical activities to equip students to master the competencies needed when working in the industrial world. Working in a practical workshop has various potential hazards, including the risk of experiencing work accidents, one of which is due to unsafe action. A preliminary survey based on the results of observations showed that out of 30 VHS students working in the practical workshop, 83.3% of them had unsafe actions such as not using personal protective equipment, as well as chatting and joking during the practical process. This study aims to determine the factors that influence unsafe action in the practical workshop of students of public vocational schools in Medan City. The study population was class XI students, totalling 164 students, with a sample size of 113 students selected by simple random sampling. This type of research is quantitative research with a cross-sectional design. The study was conducted in three Vocational Schools with mechanical engineering majors in Medan City: State Vocational School 2, State Vocational School 5, and State Vocational School 14. Data analysis was conducted univariately and bivariately, with simple and multivariate data, and with multiple logistic regression. The results showed that the majority of students had unsafe action (84.1%), as well as knowledge (60.2%) and supervision (61.1%). Supervision (p=0.012) had a relationship with unsafe action, while knowledge (p=0.143) and tools and equipment (p=0.121) did not show significant relationship. Students with poor supervision had 3.937 times (95% CI: 1.353-11.640) risk of unsafe action compared to those with good supervision. Schools are expected to increase supervision or responsibility as well as implement a reward and punishment system for students to reduce the occurrence of unsafe actions that can increase the risk of work accidents. Keyword: Knowledge, Supervision, Unsafe action, Vocational high school